Prof. Madya Fuziah Mohd. Nadzar / Aida Hafizza Sabtu and Nurul Nabilah Ibrahim - Sabtu, Aida Hafizza; Ibrahim, Nurul Nabilah (Faculty of Information Management, 2011)
Fuziah binti Mohd. Nadzar is an Associate Professor in the Faculty of Information Management, Universiti Teknologi MARA (UiTM). She was born 55 years ago in Hospital Besar, Kuala Lumpur. She received her diploma at Institut Teknologi Mara (ITM) and managed to achieve ITM's Library Science Best Student Award in 1979. After she completed her Master in Library Science at Case Western Reserve University, Cleveland, Ohio, US, she joined the School of Library Science, ITM as a young lecturer. She has been with UiTM for the past 29 years. Prof. Madya Fuziah is a hardworking person and is passionate about her work in this field. Being an Associate Professor, she is actively contributing to the Library Science field with her translation works with IFLA, books, and articles and, also being invited to conduct workshops for other organizations. Aside from that, she had achieved some awards such as Anugerah Khidmat Cemerlang UiTM for 1997 and 2009. In 2008, she was awarded Anugerah Khidmat 25 Tahun di UiTM. Prof. Madya Fuziah is hoping that the profession will be well-recognized by the society and that graduates will be catalysts for change in the field.